2005
DOI: 10.1002/ajh.20421
|View full text |Cite
|
Sign up to set email alerts
|

Isolated extramedullary relapse after autologous bone marrow transplantation for acute myeloid leukemia: Case report and review of the literature

Abstract: Isolated extramedullary relapse (IEMR) is a pattern of acute myeloid leukemia (AML) relapse post-allogeneic bone marrow transplantation (alloBMT). Less is known about IEMR post-autologous BMT (autoBMT) and about factors associated with IEMR. We report a case of a woman with M4 AML who experienced IEMR post-autoBMT and review the related literature. Seventy-two alloBMT and 3 autoBMT patients, including ours, were identified. The review suggests that an M2 or M4 French-American-British (FAB) phenotype, intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Other studies, including recent ones, have shown that EM relapse of AML occurs in 5% to 12% of patients who receive alloSCT, accounting for 7% to 46% of total relapses [7][8][9][10][11][12][13][14][15][16]. In a study that examined data from the European Bone Marrow Transplant Registry database, the incidence of EM relapse was statistically higher in patients who underwent allogeneic bone marrow (BM) transplantation than in those who underwent autologous BM transplantation (11% vs 6%; P 5 .02) [17].…”
Section: Incidence and Risk Factorsmentioning
confidence: 94%
“…Other studies, including recent ones, have shown that EM relapse of AML occurs in 5% to 12% of patients who receive alloSCT, accounting for 7% to 46% of total relapses [7][8][9][10][11][12][13][14][15][16]. In a study that examined data from the European Bone Marrow Transplant Registry database, the incidence of EM relapse was statistically higher in patients who underwent allogeneic bone marrow (BM) transplantation than in those who underwent autologous BM transplantation (11% vs 6%; P 5 .02) [17].…”
Section: Incidence and Risk Factorsmentioning
confidence: 94%
“…In the care of patients with AML-in contrast to malignant lymphoma (2)-imaging techniques based on morphologic (CT, MRI) or functional (PET, scintigraphy) alterations play only an ancillary role, for example, for management of infections or detection of uncommon manifestation sites. Extramedullary disease in lymph nodes, the central nervous system, or soft tissue seems to be of increasing significance in patients with relapse after allogeneic stem cell transplantation (3)(4)(5)(6)(7). To know about extramedullary manifestations is important for long-term disease control, because some of these sites may not be reached by standard chemotherapy.…”
mentioning
confidence: 99%
“…A major historical survey revealed that the risk factors for EMR are the M2 or M4 French-American-British (FAB) phenotype, a good or intermediate cytogenetic risk group, and busulfan usage; [13] other studies have shown that factors including a TBI-based regimen, the occurrence of GVHD [8] and prophylaxis with intrathecal chemotherapy [14] did not decrease the incidence of EMR. It is surprising that isolated EMR is also known to occur among good risk patients having t(8;21), inv (16) or t (15;17) and recipients who have undergone a myeloablative conditioning regimen [7]. To date, no single risk factor has been identified, and different pathogenetic mechanisms might be involved.…”
Section: Resultsmentioning
confidence: 99%
“…EMR is also known as ''granulocytic sarcoma'', [4] and it is designated as ''isolated'' due to the absence of BM relapse. Although some risks predisposing patients to this disease have been identified, [1,[5][6][7] many incomprehensible findings cloud the issue, and the mechanism of isolated EMR has not yet been fully described. Isolated EMR may occur regardless of whether graft-versus-host disease (GVHD) has appeared after SCT [8], and many previous reports suggest that a graft-versus-leukemia (GVL) effect at the extramedullary site may be less prominent than that in the BM [9][10][11].…”
Section: Introductionmentioning
confidence: 99%